2020
DOI: 10.1177/1747493020947333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seasonal and temperature variation on hospitalizations for stroke over a 10-year period in Brazil

Abstract: Background Seasonal variation in stroke incidence remains controversial. Aims We aimed to describe the pattern of seasonality in hospitalizations for stroke in Brazil. Methods We evaluated age-adjusted hospitalization rates for stroke per month using data from the Brazilian Unified Healthcare System and median monthly temperature data obtained from the National Institute of Meteorology. To detect a seasonality pattern in time series, we used seasonal-trend decomposition using LOESS. We calculated a seasonal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
(17 reference statements)
0
7
0
1
Order By: Relevance
“…A taxa encontrada parece alta em relação à média de hospitalizações por AVC na região Norte e no Brasil (13,0 e 8,8 por 100.000 habitantes, respectivamente). 44 No entanto, devese lembrar que limitações como o baixo número de admissão e o viés de aferição podem estar presentes neste estudo, e tais limitações reduzem o poder de comparabilidade destes dados com os de outros estudos, mesmo para aqueles com metodologias similares.…”
Section: Resultsunclassified
“…A taxa encontrada parece alta em relação à média de hospitalizações por AVC na região Norte e no Brasil (13,0 e 8,8 por 100.000 habitantes, respectivamente). 44 No entanto, devese lembrar que limitações como o baixo número de admissão e o viés de aferição podem estar presentes neste estudo, e tais limitações reduzem o poder de comparabilidade destes dados com os de outros estudos, mesmo para aqueles com metodologias similares.…”
Section: Resultsunclassified
“…Various studies from different regions of the world support a winter peak in the incidence of stroke. [4][5][6][7][8][9][10][11][12] Seasonality in several cardiovascular risk factors may explain this winter peak, specifically in the elderly population. Fibrinogen, for instance, is an independent risk factor for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…3 Seasonal variations in the incidence of stroke have been examined in numerous studies worldwide. Most studies reported a winter peak in the occurrence of stroke, [4][5][6][7][8][9][10][11][12] others found no seasonal variation [13][14][15] and fewer showed a summer peak 16 or an autumn peak. 17 Data on whether seasonality of stroke differs with age are limited.…”
Section: Introductionmentioning
confidence: 99%
“…16 Seasonal effects have been associated with the occurrence of stroke, so controls for this factor were included in the analysis. 17…”
Section: Participants and Matchingmentioning
confidence: 99%